Changes in Coral Skeleton Growth Recorded by Density Band Stratigraphy, Crystalline Structure, and Hiatuses - Fouke, Kyle W.; Trop, Jeffrey M.; Sivaguru, Mayandi (Frontiers in Marine Science, 2021)
Next-generation high resolution brightfield microscopy, x-radiography, and microcomputed tomography (microCT) analyses indicate that coral skeleton high density band (HDB) and low density band (LDB) stratigraphic sequences record dynamic changes in coral growth history. HDB-LDB sequences were studied within three small heads of Orbicella annularis, an ecological keystone species in the Caribbean Sea, collected from the leeward fringing reefs on Curaçao. Results indicate that HDB layers are formed by the thickening of skeletal components (exothecal dissepiments, costae, and theca) external to, and at the margin of, individual skeletal cups (corallites). Conversely, HDB skeletal components formed within individual corallites (endothecal dissepiments, septa, and columella) do not change thickness. HDB-LDB stratigraphic sequences were laterally traced from the center to the margins of individual coral heads, demonstrating that shifts took place in the trajectory of coral growth. Normal HDB layers are age-equivalent to surfaces of erosion and non-deposition (hiatuses) on both the center top and margins of individual heads. While multiple marine ecological processes may have led to formation these hiatuses within HDB-LDB stratal geometries, the presence of these hiatus surfaces in other large coral heads would significantly impact sclerochronology and associated sea surface temperature (SST) reconstructions.